Assessing The Nutritional Status and Health Outcomes of Women and Children in Rajshahi, Bangladesh: A Comprehensive Study - Rashed Alam; Most Tanziman Ara (International Journal of Nutrition, 2025)
Background Malnutrition is a significant public health issue in Bangladesh, particularly impacting women and children. Rajshahi, marked by socio-economic disparities, offers a distinctive context to explore the nutritional status and health outcomes of these vulnerable groups. Objectives This study aims to assess the nutritional status of women and children in Rajshahi and investigate associated health outcomes. Additionally, it seeks to identify socio-economic and cultural factors that influence nutrition. Methods A mixed-methods approach was utilized, incorporating a cross-sectional survey of 460 households and in-depth interviews with mothers and caregivers. Anthropometric measurements were taken to evaluate the nutritional status of women and children, while dietary assessments measured nutrient intake and diversity. Logistic regression analysis was performed to determine the likelihood of malnutrition based on socio-economic characteristics, thereby identifying key risk factors. Results The findings indicate a troubling prevalence of malnutrition, with 36% of children under five classified as stunted and 25% as underweight. The analysis highlights critical factors contributing to chronic undernutrition, including maternal education, employment, and dietary diversity. Notably, mothers aged 27-37 exhibit a lower risk of undernutrition, and urban households with secure food access demonstrate better nutritional outcomes. Discussion Maternal education and employment were positively associated with better nutritional outcomes, as educated and employed mothers had higher chances of maintaining a normal BMI. Regular ANC visits (≥4 visits) were crucial for improved maternal nutrition. Household food security emerged as a significant determinant, with food-secure households showing better maternal nutritional status. Safe water access and adequate dietary diversity were also linked to improved maternal BMI. Additionally, factors such as child birth weight, exclusive breastfeeding, and childhood diarrhea significantly influenced maternal nutrition. Moreover, frequent antenatal care visits and a diverse diet are vital in mitigating undernutrition risks among children. Conclusion This study emphasizes the urgent need for targeted interventions to combat malnutrition in Rajshahi. Recommendations include implementing community-based nutrition education programs and improving access to healthcare services. By addressing the socio-economic and cultural determinants of nutrition, stakeholders can enhance health outcomes for women and children in the region, ultimately contributing to broader public health objectives in Bangladesh.
Keywords: Socioeconomic inequalities